Fairness for Children - UNICEF Innocenti Research Centre (United Nations, 2016)
This Report Card presents an overview of inequalities in child well-being in 41 countries of the European Union (EU) and the Organisation for Economic Co-operation and Development (OECD). It focuses on ‘bottom-end inequality’ – the gap between children at the bottom and those in the middle – and addresses the question ‘how far behind are children being allowed to fall?’in income, health and life satisfaction.